Visible Spectrophotometric Estimation of Tenoxicam from Tablets. - Panwar, Mangal (International Journal of Pharmaceutical & Biological Archive, 2010)
A simple, Precise, accurate, fast and economical methods have been developed for the quantitative estimation of Tenoxicam from tablet formulation using Ferric chloride and 1, 10 phenanthroline. Tenoxicam forms a red colored chromogen with the reagent, which shows absorbance maxima at 490.5 nm and linearity in the concentration range of 8-40 µg/ml of drug. The results of analysis for the methods were validated statistically and by recovery studies.